Implications of Principals’ Transformational Leadership on the Work Motivation of Generation Z Teachers at SDN 2 Senawar - Dwi Nuriyah; Rd. M. Ali; Masbirorotni Masbirorotni (Journal of Educational Sciences, 2026)
This study aims to examine the implementation of principals’ transformational leadership in improving the work motivation of Generation Z teachers at SDN 2 Senawar. This study employed a qualitative descriptive approach. Data were collected through in-depth interviews with the principal and twelve Generation Z teachers, supported by observation and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that the principal applies transformational leadership through four dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. These practices contribute positively to enhancing teachers’ motivation, job satisfaction, sense of belonging, and performance. The use of technology, open communication, and constructive feedback are key factors in strengthening intrinsic motivation. The study concludes that adaptive and collaborative transformational leadership is effective in addressing the characteristics and needs of Generation Z teachers in elementary schools.